2017
DOI: 10.1095/biolreprod.116.143834
|View full text |Cite
|
Sign up to set email alerts
|

Augmented H2S production via cystathionine-beta-synthase upregulation plays a role in pregnancy-associated uterine vasodilation†

Abstract: Endogenous hydrogen sulfide (H2S) synthesized via metabolizing L-cysteine by cystathionine-beta-synthase (CBS) and cystathionine-gamma-lyase (CSE) is a potent vasodilator and angiogenic factor. The objectives of this study were to determine if human uterine artery (UA) H2S production increases with augmented expression and/or activity of CBS and/or CSE during the menstrual cycle and pregnancy and whether exogenous H2S dilates UA. Uterine arteries from nonpregnant (NP) premenopausal proliferative (pPRM) and sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
99
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(119 citation statements)
references
References 45 publications
16
99
4
Order By: Relevance
“…E 2 β also stimulates CSE mRNA and protein expressions in UASMCs in vitro. This observation is unexpected because it not only contrasts to our in vivo findings that UASMC CSE mRNA and protein are not altered by estrogens in sheep (Lechuga et al, 2015) and women (Sheibani et al, 2017), but also other reports showing that E 2 β does not stimulate CSE expression in mouse mesenteric artery SMCs in vitro . Although the mechanisms underlying this discrepancy between the in vitro and in vivo findings is elusive, this raises a (Liao et al, 2005).…”
Section: Discussioncontrasting
confidence: 94%
See 2 more Smart Citations
“…E 2 β also stimulates CSE mRNA and protein expressions in UASMCs in vitro. This observation is unexpected because it not only contrasts to our in vivo findings that UASMC CSE mRNA and protein are not altered by estrogens in sheep (Lechuga et al, 2015) and women (Sheibani et al, 2017), but also other reports showing that E 2 β does not stimulate CSE expression in mouse mesenteric artery SMCs in vitro . Although the mechanisms underlying this discrepancy between the in vitro and in vivo findings is elusive, this raises a (Liao et al, 2005).…”
Section: Discussioncontrasting
confidence: 94%
“…In cells expressing both ERα and ERβ, including UASMCs they can play similar or even opposite roles in mediating estrogen signaling (Zhang, Feng, Wang, Magness, & Chen, 2012 (Zhang et al, 2012). E 2 β stimulates both mRNA and protein expressions of CBS and CSE in vitro (current study) and CBS in vivo (Lechuga et al, 2015;Sheibani et al, 2017), suggesting that these stimulations occur at the level of transcription. Indeed, E 2 β stimulates > 4-fold increases in CBS and CSE promoter activity in UASMCs in vitro (Figure 4a).…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…In mammals, H 2 S potently dilates various vasculatures via activating ATP-dependent potassium (K ATP ) channel [21] and relaxes smooth muscle via activating large conductance calcium-activated potassium (BK Ca ) channel [22]. We recently reported that a slow-releasing H 2 S donor GYY4137 dose-dependently relaxes UAs from nonpregnant and pregnant rats, with significantly greater potency in the pregnant state and vascular bed specificity [23]. Others have shown H 2 S to be a placental vasodilator [24,25] and dysregulated CTH/H 2 S signaling in the placenta results in preeclampsia-like conditions [25].…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen sulfide (H 2 S) is produced endogenously in mammals by metabolism of sulfur-containing amino acids under the catalysis of special enzymes ( Predmore et al, 2012 ; Sheibani et al, 2017 ) and has been regarded as the third bio-active gas or gaseous signaling molecule by accumulated evidence ( Gadalla and Snyder, 2010 ; Predmore et al, 2012 ; Yu et al, 2017 ). H 2 S plays important physiological and pathological roles in many biological processes and acts as a critically functional regulator in several brain regions, such as the hippocampus and cerebral cortex ( Giuliani et al, 2013 ; Yakovlev et al, 2017 ; Zhu et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%